The Elias enigma : a Caspian Anderson thriller - Gervais, Simon (Caspian Anderson thriller, 2025)
"Caspian Anderson, once a black-ops assassin known as Elias, now works for the Defense Clandestine Service. But unfinished business dies hard. Glimpsing a familiar face while tying up loose ends overseas, he swears it's his lover, Liesel Bergmann-a German spy and erstwhile collaborator. But back stateside, he can't ask her without giving himself away. This mystery hangs between them as they kick off a new mission together: to unravel a global criminal conspiracy, one that implicates Caspian's own parents. Dispatched to France, they must track down rogue start-up founder Frank LaBelle before his cutting-edge defense tech falls into the wrong hands. But when Caspian's team is compromised by friends and foes, he's left with no one to trust but himself. And to complete the mission-and save the world-he resurrects the deadly Elias."